P211 Time-Course of Rhinovirus and Bacterial Infection During COPD Exacerbation Recovery. (19th November 2012) - George, SN; Garcha, DS; Patel, ARC; Mackay, AJ; Singh, R; Sapsford, RJ; Donaldson, GC; Wedzicha, JA
Abstract : Introduction: Airway bacteria and viruses are aetiological triggers of COPD exacerbations. Changes in prevalence of rhinovirus and typical airway bacteria together have not been examined during COPD exacerbation recovery. We compared the prevalence of the clinically relevant microorganisms (CRMs) human rhinovirus and typical pathogenic bacteria ( H. influenzae, M. catarrhalis and S. pneumoniae ) at five time points during COPD exacerbation recovery. Methods: London COPD cohort patients recorded any new or increased respiratory symptoms on daily diary cards and contacted the clinical team when symptoms worsened. Exacerbations were defined using our usual symptomatic criteria; an increase in respiratory symptoms for two consecutive days, with at least one symptom being major (dyspnoea, sputum purulence or volume) and the other a major or minor symptom (wheeze, cold, sore throat, cough). Reverse-transcription quantitative PCR was used to detect rhinovirus and real-time quantitative PCR was utilised to identify typical bacteria in sputum samples collected at exacerbation presentation (median 2 days after symptom onset), and at days 3, 7, 14 and 35 post-presentation. Results: Nineteen patients with moderate to severe COPD (mean age 68.8 years (SD±8.1); FEV1 48.4% predicted (±19.2%); current smoker 37%; FEV1/FVC 0.46 (SD±0.14); FEV1 1.2L (SD±0.4); male gender 74%) provided 89 of 110 potential sputum samples at 5 time points during 22 exacerbations. Rhinovirus prevalence progressively fell from 71.4% at exacerbation presentation to 0% at day 35 with significant decreases in prevalence between presentation and days 7, 14 and 35 (all p<0.002) (Figure 1 ). No exacerbation was negative for rhinovirus detection at presentation but positive at later time points. For typical bacteria, 64.7% of samples taken at presentation were positive. This proportion fell at days 3 and 7 but these falls were non-significant (p=0.08 and p=0.09, respectively) – all events were treated with antibiotics. Seven of the 22 exacerbations (31.8%) were positive for both CRMs at presentation. Conclusion: The prevalence of CRMs varies during recovery from a COPD exacerbation. Rhinovirus prevalence steadily decreases over 2 weeks whilst bacterial prevalence is more variable, presumably due to the background effects of lower airway bacterial colonisation. This emphasises the importance of rhinovirus as a major exacerbation trigger.